Commentary on effectiveness of early lens extraction for the treatment of primary angle-closure glaucoma (EAGLE) - Chan, Poemen P.; Tham, Clement C. (Annals of Eye Science, 2017)
Relative pupil block is the most common mechanism of intraocular pressure (IOP) elevation in primary angle-closure glaucoma (PACG) and primary angle closure (PAC). The standard approach of treating PACG and PAC is laser peripheral iridotomy (LPI) with or without additional IOP-lowering agents. If IOP remains poorly controlled, lens removal could be considered, especially if the patient has co-existing symptomatic cataract. The efficacy of lowering IOP by lens extraction for patients with co-existing cataract and PACG or PAC is known (1-4). Some authors had suggested an early lens extraction approach as the treatment of choice for PACG (5,6). However, the justification of performing clear-lens extraction as first-line treatment instead of LPI for this group of patients, who have satisfactory visual acuity, is often obviated by the concern of potentially serious complications, such as malignant glaucoma. There has been no randomised control trial to justify clear-lens extraction as the first-line treatment in clinical practice.